Narrative Analysis of Childbearing Experiences During the COVID-19 Pandemic. Issue 5 (September 2021) - Ajayi, Kobi V.; Harvey, Idethia S.; Panjwani, Sonya; Uwak, Inyang; Garney, Whitney; Page, Robin L.
Abstract: Purpose: The COVID-19 pandemic has disrupted health care delivery and services around the world causing rapid changes to maternity care protocols and pregnant women to give birth with tight restrictions and significant uncertainties. There is a gap in evidence about expectant and new mothers' experiences with birthing during the pandemic. We sought to describe and understand pregnant and new mothers' lived experiences during the COVID-19 pandemic using authentic birth stories. Study Design and Methods: Using a narrative analysis framework, we extracted relevant YouTube birth stories using predetermined search terms and inclusion criteria. Mothers' birth stories were narrated in their second or third trimester or those who had recently given birth during the pandemic. Birth stories were analyzed using an inductive and deductive approach to capture different and salient aspects of the birthing experience. Results: N = 83 birth stories were analyzed. Within these birth stories, four broad themes and 13 subthemes were identified. Key themes included a sense of loss, hospital experiences, experiences with health care providers, and unique experiences during birth and postpartum. The birth stories revealed that the COVID-19 pandemic brought unexpected circumstances, both positive and negative, that had an impact on mothers' overall birthing experience. Clinical Implications: Results provided a detailed description of women's lived experience with giving birth during the COVID-19 pandemic. Maternity nurses should try to provide clear communication and compassionate patient-centered care to relieve women's anxieties about uncertain and unpredictable policy changes on COVID-19 as the pandemic continues to evolve. Abstract : The COVID-19 pandemic has disrupted health care delivery and services around the world causing rapid and constant changes to maternity care protocols and pregnant women to give birth with restrictions and significant uncertainties. In this study, mothers' birth stories during the pandemic that were posted to YouTube were analyzed. Rich detailed description of women's lived experience with giving birth during the COVID-19 pandemic are presented along with suggestions for nurses to minimize the stress of the vagueness and ambiguity of hospital restrictive practices during the childbirth process in the context of the pandemic.